PERAN KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI BERPRESTASI DALAM MENINGKATKAN KINERJA PEGAWAI DENGAN MEDIASI KOMITMEN AFEKTIF PADA PUSKESMAS KECAMATAN NGALIYAN KOTA SEMARANG - Astrakusuma, Abdul Rahman; Asyhari (Universitas Bina Taruna Gorontalo, 2025)
This research aims to analyze the influence of transformational leadership and achievement motivation on the performance of health center employees in Ngaliyan District, Semarang City and to see whether there is an influence of affective commitment as an intervening variable. Data were collected using a questionnaire with a purposive sampling technique. The population in this study was 173 employees spread across three health centers in the Ngaliyan District, Semarang City, taken as a sample of 154 employees. Data processing using SEM-PLS analysis. Hypothesis testing uses two criteria, namely if t-statistics or the critical value is more than 1,96 then the hypothesis is accepted or when p-value less than 0.05 then the hypothesis is accepted. The results of the study indicate that transformational leadership does not affect employee performance, either directly or through the mediation of affective commitment. Achievement motivation has a significant effect on employee performance, either directly or through the mediation of affective commitment. These findings provide an illustration that the influence of transformational leadership on performance is not absolute and can vary depending on the organizational context, work culture, and employee perceptions.